"Unveiling the Impact: Examining the Role of Internet in Architecture through Post-Occupancy Analysis and User Satisfaction in DHA Lahore" (International Journal of Architecture and Urbanism, 2023)
This qualitative research paper explores the impact of internet connectivity in architecture, specifically within the context of DHA Lahore. Adopting a post-occupancy analysis approach, the study examines the role of internet technology in architectural design and its influence on user satisfaction within the DHA Lahore community. Through in-depth interviews, observations, and document analysis, this research investigates the experiences and perceptions of residents regarding the use of internet in architectural spaces. It explores how internet connectivity affects their daily lives, communication patterns, access to information, and overall satisfaction with the built environment in DHA Lahore. The study delves into the ways in which internet connectivity is integrated into architectural design, including considerations such as accessibility, reliability, and user-friendliness. By analyzing qualitative data, the research uncovers the benefits and challenges associated with internet connectivity in architectural spaces, as perceived by the users in DHA Lahore. Furthermore, the paper explores the impact of internet connectivity on various architectural elements, such as space utilization, collaboration, and smart home technologies. It investigates how these elements, when enhanced by internet connectivity, contribute to user satisfaction and the overall quality of life in DHA Lahore. By utilizing a qualitative methodology, this research offers rich insights into the lived experiences and perspectives of users in DHA Lahore. It provides a deeper understanding of the ways in which internet connectivity influences architectural design and user satisfaction, highlighting potential areas for improvement and innovation.